Development of nomogram for the practical mix design of steel fiber reinforced concrete - Ulas, Merve Acikgenc; Alyamac, Kursat Esat; Ulucan, Zulfu Cinar (Elsevier Sci Ltd, 2018)
Steel fiber reinforced concrete (SFRC) is a special type of concrete of which the use of this concrete type is growing up. With the wide using of SFRC, some requirements have emerged. One of these requirements is a practical mix design of SFRC. In this study, it is aimed to produce an effective mix design nomogram, including both fresh and hardened properties of SFRC, simultaneously. With this aim, the relationships between mixture proportions, fresh and hardened properties of SFRC were revealed with the convenient graphics, and these were brought together to create a nomogram. As different from previous studies, two most important superior mechanical properties of SFRC such as flexural strength and modulus of toughness were included in the developed mix design nomogram. As a conclusion, two nomograms which help to accurately and practically estimate mix design of SFRC with aimed properties were revealed. Using these nomograms, at academic milieu and institutions for SFRC, it can be possible to minimize loss of material and time during trial-and-error sample production. Thus, the production process of SFRC can be achieved more practically and economically. (C) 2018 Elsevier Ltd. All rights reserved.
Keywords: Steel fiber reinforced concrete; Mix design; Nomogram; Flexural strength; Toughness